Enforcement of intellectual property rights - Mertha, A (Foundation for Law, Justice and Society, 2007)
This brief adopts a neo-institutional approach to derive some generalizations about how China’s policies are enforced, why enforcement remains such a problem, and what foreign firms can do to meet the challenges provided by China’s enforcement regime. In particular, the brief draws on the protection of intellectual property rights to illustrate the following. Formal administrative rank is an important shorthand for understanding the power relations between two or more bureaucracies and/or regional governments. This has an important bearing on enforcement. Given the chronically overstretched resources of the courts in China and the hierarchical structure of the administration, policy priorities are particularly susceptible to manipulation by unscrupulous commercial concerns. It is important to identify trends of decentralization, as well as more recent trends of centralization, to determine the power relationships in a given policy enforcement context. The scope of action of subordinate agencies is critically affected by the degree of dependence on, or independence from, superior or host units. Insofar as China’s institutions remain in flux, personal power can replace institutional mandates with regard to ultimate decision making. It is, therefore, critical to identify the juncture at which individuals matter and to take that into account when evaluating a given enforcement context.